Alternative journalism education in Turkey: a case study of the 'From School to Newsroom' (OHO) program - Sen, Ayse Fulya (Palgrave Macmillan Ltd, 2017)
Alternative media challenges the practices of established mainstream journalism and institutionalised politics. Alternative media presents a radical challenge to the institutionalised and professionalised mainstream media and provides a perspective that is dedicated to notions of social responsibility by replacing the ideology of objectivity with overt advocacy and oppositional practices. As an alternative media platform, the BIA (The Independent Communication Network), is a project that attempts to strengthen the independent media, which aims to carry the entire communication process beyond daily news production. Under the program Okuldan Haber Odasina (OHO) (From Classroom to Newsroom) arranged by the BIA, academics and professional journalists deliver lectures to journalism students. During this education process, students have the opportunity to observe various media and rights organizations. This study aims to draw attention to the necessity of a critical perspective in journalism education and to discuss how alternative journalism can transform the existing practices, values and ideologies and to illustrate the importance of alternative media in the societies surrounded by capitalist social and economic values. In addition, this article contributes to journalism studies with a discussion of the importance of critical thought in constructing democratic and pluralist perspective in the news media through an education model.
Keywords: Media